Regeneration Potential of Mid-hill Himalayan Grasslands of Idmachal Pradesh - Misri, Bimal; Sareen, Sindhu (Indian Forester, 2004)
The utilization pattern of mid-hill.. Himalayan grasslands in Himachal Pradesh is traditional. This grasslands are closed to grazing before onset of monsoon in the month of June and the herbage harvested in October , is conserved for use during winter. The grasslands are then opened for indiscriminate grazing till next monsoon. Thus , the total biomass available is 1.0-2.0 tlha (dry matter). However , the present study undertaken at Palampur during 1997-98 on a well protected grassland revealed that the grasslands have the potential to provide herbage under frequent cuttings , if they are protected from grazing. Under monthly cutting regimes biomass up to 79.53 t/ha (green) and 15.98 t/ha (dry) was obtained during 1997-1998.